Recanalization rate of proximal deep venous thrombosis related to therapeutic modality during six months follow-up - Alden Begić; Edin Begić; Mirza Dilić; Svjetlana Loga-Zec; Nermina Babić; Refet Gojak; Armin Šljivo (Medicinski glasnik, 2022)
Aim: To evaluate the efficacy (rate of recanalization) of therapy with novel oral anticoagulants (NOAC; rivaroxaban, apixaban) compared to conventional treatment (low molecular weight heparin - LMWH and vitamin K antagonist) in the treatment of deep vein thrombosis (DVT) of the proximal segments of lower extremities. Methods: The first group consisted of patients diagnosed with DVT and treated with NOAC (n = 100), while the second group consisted of patients diagnosed with DVT, who were treated by conventional treatment (low molecular weight heparin and vitamin K antagonists) (n = 100). In the first group, NOAC was included in the initial treatment. Patients in the second group were treated with LMWH for four days, and on the fifth day vitamin K antagonist was included in therapy, international ratio (INR) was titrated to therapeutic values (2.0-3.0), and then low molecular weight heparin was excluded from the therapy. Results: There was a statistically significant difference in the estimated values of free lumen of the blood vessel between the examined groups after 30 days (p=0.0001), after 90 days (p=0.0001) and after 180 days (p=0.0001). After 180 days, the average free lumen values in the NOAC group were 85% (81-89%), which was significantly higher than the free lumen values in the second group, 73% (69-79%). Conclusion: The use of NOAC represents more efficient treatment of DVT comparing to vitamin K antagonists.
Keywords: anticoagulants; therapeutics; veins